STUDENTS’ PERSPECTIVES OF UTILIZING HELLO ENGLISH APPLICATION FOR ENGLISH VOCABULARY LEARNING: A QUALITATIVE CASE STUDY - Rahman , Bonza Sheilla Luthfia; Nabhan, Salim (ENGLISH JOURNAL, 2023)
Nowadays the use of technology media is inevitable in EFL classrooms. However, the study pertaining to the use of the Hello application that focuses on learning vocabulary is still relatively limited. Therefore, this study aims to explore students’ perspectives on using the Hello English application for English vocabulary learning. This research used a qualitative case study. The data were collected through interviews, observation, and document reviews from the 9th-grade students at a state junior high school in Sidoarjo, East Java, Indonesia. The data were then analyzed using thematic analysis. The result revealed two main themes: the benefits and concerns associated with using the Hello English application for vocabulary learning. The students perceived benefits of the application including improving their understanding, pronunciation, and expansion of English vocabulary, along with enjoyable learning experiences. However, students encountered challenges, such as technical difficulties and struggles with advanced games. In addition, the students overcame these issues with the assistance of others. The study might have implications on the understanding of the enactment in using the technological application for EFL vocabulary learning.